2021
DOI: 10.1097/ana.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Cerebral Oxygen Saturation Effect of Inotropes/Vasopressors Administered to Treat Intraoperative Hypotension: A Bayesian Network Meta-analysis

Abstract: One of the main concerns of intraoperative hypotension is adequacy of cerebral perfusion, as cerebral blood flow decreases passively when mean arterial pressure falls below the lower limit of cerebral autoregulation. Treatment of intraoperative hypotension includes administration of drugs, such as inotropes and vasopressors, which have different pharmacological effects on cerebral hemodynamics; there is no consensus on the preferred drug to use. We performed a network meta-analysis (NMA) to pool and analyze da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…We read with great interest the study by Koch et al ., 1 which concluded that “ephedrine results in better brain microcirculation and oxygen delivery than phenylephrine” and raised “concerns regarding phenylephrine for blood pressure augmentation in patients with cerebral pathology.” The results of this prospective, randomized trial are similar to those of a network meta-analysis 2 of 399 patients from nine randomized trials comparing various inotropes/vasopressors used to treat intraoperative hypotension in patients mostly without cerebral pathology. That analysis found that dopamine, ephedrine, and norepinephrine had the lowest probability of adversely affecting cerebral oxygen saturation as measured by cerebral oximetry and that phenylephrine, compared with the other inotropes/vasopressors, decreased cerebral oxygen saturation.…”
Section: To the Editorsupporting
confidence: 59%
“…We read with great interest the study by Koch et al ., 1 which concluded that “ephedrine results in better brain microcirculation and oxygen delivery than phenylephrine” and raised “concerns regarding phenylephrine for blood pressure augmentation in patients with cerebral pathology.” The results of this prospective, randomized trial are similar to those of a network meta-analysis 2 of 399 patients from nine randomized trials comparing various inotropes/vasopressors used to treat intraoperative hypotension in patients mostly without cerebral pathology. That analysis found that dopamine, ephedrine, and norepinephrine had the lowest probability of adversely affecting cerebral oxygen saturation as measured by cerebral oximetry and that phenylephrine, compared with the other inotropes/vasopressors, decreased cerebral oxygen saturation.…”
Section: To the Editorsupporting
confidence: 59%
“…Bombardieri et al conducted a Bayesian network meta-analysis of available RCTs comparing the effect of various inotropes and/or vasopressors used to treat intraoperative hypotension on cerebral oxygen saturation (ScO 2 ) measured by cerebral oximetry. 8 Nine RCTs were included (6 studies were in non-neurological surgeries, 2 in carotid endarterectomy, and 1 in craniotomy) and pooled analysis showed that dopamine, ephedrine, and norepinephrine had the lowest probability of decreasing ScO 2 . The suggested rank order to use to maintain ScO 2 during perioperative hypotension, from higher to lower, was respectively dopamine, ephedrine, norepinephrine, and phenylephrine.…”
Section: Effect Of Inotropes and Vasopressors On Cerebral Oxygen Satu...mentioning
confidence: 99%
“…2 We agree with Bombardieri and Tsui that the deterioration of microperfusion and possibly tissue oxygenation after phenylephrine administration in the “healthy” brain hemisphere 2 indicates that different vasopressors may also have a different influence on microperfusion and tissue oxygenation in the healthy anesthetized brain and should be further explored. 3 In our opinion, future studies on the effects of different vasopressors on the cerebral macro- and microcirculation should be considered in the context of their different effects on the systemic circulation to provide a fully integrated picture of their influence on organ perfusion and oxygenation. 4 Due to current difficulties in monitoring brain microcirculation and cerebral tissue oxygenation, we tend to rely on systemic parameters such as heart rate and blood pressure when treating patients with inotropes/vasopressors.…”
Section: In Replymentioning
confidence: 99%